Effects of triolein dilution on the structural and mechanical properties of lauric acid-rich fat. (October 2021) - Chai, Xiuhang; Meng, Zong; Liu, Yuanfa
Abstract: Understanding fat structure and mechanical properties is crucial for the processing and mouthfeel of fat-rich foods. In this study, we systematically explored the impact of changes in the composition of fully hydrogenated palm kernel oil (FHPKO) on its crystallization behavior, nano/microstructure, and mechanical properties by blending with 1, 2, 3, 4, 5, 10, and 20% triolein (OOO). Changes in the triglycerides (TAGs) composition of FHPKO affected its crystal habit and therefore its functionality. The lower melting unsaturated OOO remarkably increased the onset of crystallization temperature and time of FHPKO, particularly with the addition of 10% and 20% OOO. The addition of OOO also slowed down the nucleation and crystal growth rate owing to the dilution of the high-melting point TAGs. X-ray diffraction analysis showed a similar lamellar longitudinal size for all fat blends. However, the crystal domain size increased with the addition of OOO, which was caused by an increase in the amount of liquid oil between the lamellae. In addition, large crystal particles were observed with an increase in OOO content, leading to a weak interaction between the clusters with a low fractal dimension, thus reducing the strength of the mechanical properties of the fat crystal network. Graphical abstract: Image 1 Highlights: Triolein delayed the nucleation and crystal growth process of FHPKO. Crystal domain size increased with more liquid oil between the lamellae. Triolein induced larger crystal particles in microstructure with smaller D b . Strength of fat network reduced by triolein, decreasing elasticity and firmness.